Characterization of the pattern of expression of Gas1 in the kidney during postnatal development in the rat. - Andrea Cetina-Palma; Carmen Namorado-Tónix; Rafael Rodríguez-Muñoz; Paula Vergara; José Luis Reyes-Sánchez; José Segovia (PLoS ONE, 2023)
Growth Arrest-Specific 1 (Gas1) is a pleiotropic protein with different functions, in the adult kidney Gas1 acts as an endogenous inhibitor of cell proliferation but it is also necessary for the maintenance and proliferation of Renal Progenitor Cells (RPC) during early development, thus it fulfills important functions in the adult kidney. However, it is not known whether or not Gas1 is expressed during postnatal development, a critical stage for renal maturation. For this reason, the main objective of this work was to characterize the expression pattern of Gas1 in the different regions of the kidney by immunofluorescence and Western blot analysis during the postnatal development of the rat. We found that Gas1 is present and has a differential expression pattern in the various regions of the nephron during postnatal development. We observed that the highest levels of expression of Gas1 occur in the adult, however, Gas1 is also expressed in RPC and interestingly, the expression of RPC markers such as the Neural cell adhesion molecule (NCAM) and Cluster of differentiation 24 (CD24) were found to have an inverse pattern of expression to Gas1 (decreases as the kidney matures) during postnatal renal maturation, this indicates a role for Gas1 in the regulation of renal cell proliferation at this stage of development.